Pengaruh Pengawasan Terhadap Kinerja Pegawai Pada Unit Pelaksana Teknis Daerah (UPTD) Pasar Penyembolum Senaken Kabupaten Paser - Syifi Fauziyah; M. Yunus Syam; Welda Widya Hidayah (Epsilon Journal of Management, 2024)
The aim of this research is to determine the effect of supervision on employee performance at the Regional Technical Implementation Unit (UPTD) Pemembolum Senaken Market, Paser Regency. From the results of the validity test, all 10 statement items were declared valid because they were greater than the rtable value of 0.2006 for each statement in this study. From the results of the reliability test, a value of 0.959 was obtained, which means there is a very strong relationship between the independent variable and the dependent variable. From the results of multiple linear regression analysis, it can be seen that the results of the regression equation are Y = 40.597 + 0.535X1 + 0.361X2. Based on the calculation results, an R value (Correlation Coefficient) of 0.915 is obtained which is at an interpretation level between 0.80-1.00, which means that there is a very strong influence from the supervision variable (X) which consists of direct supervision (X1), and supervision. indirectly (X2), on employee performance (Y).